1987
DOI: 10.1104/pp.85.4.1129
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Transport in Sealed Vesicles from Red Beet (Beta vulgaris L.) Storage Tissue

Abstract: Calcium transport was examined in microsomal membrane vesicles from red beet (Beta vulgaris L.) storage tissue using chlorotetracycline as a fluorescent probe. This probe demonstrates an increase in fluorescence corresponding to calcium accumulation within the vesicles which can be collapsed by the addition of the calcium ionophore A23187. Calcium uptake in the microsomal vesicles was ATP dependent and completely inhibited by orthovanadate. Centrifugation of the microsomal membrane fraction on a linear 15 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 20 publications
(32 reference statements)
3
37
2
Order By: Relevance
“…However, although previous phosphorylation studies in red beet were conducted in the presence of calcium (Giannini et al, 1987a;Williams et al, 1990), the calcium-dependence of the phosphoenzymes observed in the Suc-gradient-enriched ER fractions (Giannini et al, 1987a) and plasma membrane fractions (Williams et al, 1990) was not established, since the phosphoenzymes were not characterized in detail. In addition, assigning a Plant Physiol.…”
Section: J53mentioning
confidence: 99%
See 2 more Smart Citations
“…However, although previous phosphorylation studies in red beet were conducted in the presence of calcium (Giannini et al, 1987a;Williams et al, 1990), the calcium-dependence of the phosphoenzymes observed in the Suc-gradient-enriched ER fractions (Giannini et al, 1987a) and plasma membrane fractions (Williams et al, 1990) was not established, since the phosphoenzymes were not characterized in detail. In addition, assigning a Plant Physiol.…”
Section: J53mentioning
confidence: 99%
“…In most reports characterizing calcium transport at particular cell membranes, the membrane fractions were isolated by discontinuous Suc gradients (Evans et al, 1991); this includes previous studies of the transporters at the ER and plasma membrane of red beet (Beta vulgaris) (Giannini et al, 1987a(Giannini et al, , 1987bWilliams et al, 1990). However, a comparison of the properties of the calcium transporters at particular cell membranes is complicated because these fractions show some degree of cross-contamination (Giannini et al, 1987a).…”
Section: J53mentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain microsomes the pellet was resuspended in a minimal volume of conservation buffer (10 mM Tris, 10 mM borate, 300 mM Suc, 9 mM KCl, 5 mM EDTA, 5 mM EGTA, 50 mM NaF pH 8.3, 4.2 mM leupeptine, 1 mM phenylmethylsulfonyl fluoride, 5 mM dithiothreitol) and frozen at 280°C. For plants grown in hydroponic, microsomes were purified as described by Giannini et al (1987).…”
Section: Nar21 and Nrt21 Immunodetection And Membrane Purificationmentioning
confidence: 99%
“…The presence of highly active Ca 2ϩ sequestration mechanisms (21)(22)(23)(24) and Ca 2ϩ channels, including ligand-gated channels (3,4,25,26), underlines the importance of Ca 2ϩ metabolism in these experimental systems.…”
mentioning
confidence: 99%